Strategi Sukses Wirausaha Perempuan Menghadapi Tantangan dan Peluang di Bulan Ramadhan - Juliyani, Erly (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Ramadan is a special month for Muslims around the world, including Indonesia. During the month of Ramadan, Muslims will fast and increase their worship and good deeds. However, the month of Ramadan can also provide opportunities and challenges for the business world. especially for female entrepreneurs so that female entrepreneurs need to understand the cultural and religious context that surrounds the month of Ramadan, while still adapting to the ever-changing dynamics of business. This involves culturally sensitive marketing strategies, adjustments to operating hours, and innovations in offering products or services that suit consumer needs during the fasting month. In this study, a descriptive qualitative approach was used, data was obtained using observation, interview, and documentation methods. Furthermore, the data was analyzed through several stages starting from data collection, data reduction, data presentation and drawing conclusions. Then data triangulation was carried out to test the validity of the data. The results of this study indicate that women have great potential to achieve their success. Although faced with various challenges and obstacles such as changes in consumption patterns and limited time, women can take advantage of opportunities by implementing smart and innovative strategies. Some strategies that can help women face challenges and maximize business opportunities during the month of Ramadan include: a deep understanding of consumer needs and preferences during the month of Ramadan, flexibility in adjusting operating hours and marketing strategies, creativity in developing products and services that are in line with the Ramadan theme.